2016
DOI: 10.1093/intqhc/mzw109
|View full text |Cite
|
Sign up to set email alerts
|

The influence of emergency department crowding on the efficiency of care for acute stroke patients

Abstract: Although ED crowding was not associated with delayed DTN, it predicted delayed DTA and DTCT in thrombolysis-eligible stroke patients. The number of attending physicians affected initial assessment and DTCTs, whereas the number of nurses impacted thrombolytic administration times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 21 publications
0
21
0
1
Order By: Relevance
“…Effects on patients included delays in being assessed and receiving required care [ 29 , 30 , 76 79 , 81 , 83 , 84 , 87 , 90 , 91 , 93 , 94 , 97 , 98 , 103 , 104 ], increased frequency of exposure to error [ 18 ], including medication errors [ 17 ], reduced patient satisfaction [ 102 ], increased inpatient length of stay (IPLOS) [ 82 , 88 , 95 , 99 , 101 ] and poorer outcomes [ 29 , 30 , 75 , 92 , 107 ]; the latter included increased inpatient mortality [ 3 , 80 , 85 , 96 , 99 101 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effects on patients included delays in being assessed and receiving required care [ 29 , 30 , 76 79 , 81 , 83 , 84 , 87 , 90 , 91 , 93 , 94 , 97 , 98 , 103 , 104 ], increased frequency of exposure to error [ 18 ], including medication errors [ 17 ], reduced patient satisfaction [ 102 ], increased inpatient length of stay (IPLOS) [ 82 , 88 , 95 , 99 , 101 ] and poorer outcomes [ 29 , 30 , 75 , 92 , 107 ]; the latter included increased inpatient mortality [ 3 , 80 , 85 , 96 , 99 101 ].…”
Section: Resultsmentioning
confidence: 99%
“…Findings were predominantly adverse, with crowding associated with delays in time to receive analgesic [ 79 , 87 , 91 , 93 ] and antibiotic therapy [ 76 , 77 , 89 , 90 , 98 ], as well as delays in patients receiving their usual prescribed or ‘home’ medications [ 83 ]. Two studies reported negative impacts of crowding on timely care for patients with acute stroke [ 94 , 103 ]. One study reported significant delays in triage times, with a significant number of patients not assigned any triage score in times of crowding [ 104 ].…”
Section: Resultsmentioning
confidence: 99%
“…[1,2] The imbalance of supply and demand in ED capacity can result in hazardous effects both on physicians and patients, [3] and previous studies have found that overcrowded ED conditions increased physician decision-making time, [4,5] led to more medication errors, [6] decreased quality of care, [7] and increased mortality during hospital stay. [8,9] These potential dangers can be particularly detrimental for patients who needed time-critical interventions to effectively treat emergency conditions such as acute stroke, [4] acute respiratory failure, [10] and septic shock. [11] Cardiac arrest is a critical situation requiring prompt intervention and continues to be a major public health burden.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] The imbalance of supply and demand in ED capacity can result in hazardous effects both on physicians and patients, [3] and previous studies have found that overcrowded ED conditions increased physician decision-making time, [4] led to more medication errors, [5] decreased quality of care, [6] and increased mortality during hospital stay. [7,8] These potential dangers can be particularly detrimental for patients who needed time-critical interventions to effectively treat emergency conditions such as acute stroke, [9] acute respiratory failure, [10] and septic shock. [11] In-hospital cardiac arrest is a critical situation requiring prompt intervention and continues to be a major public health burden.…”
Section: Introductionmentioning
confidence: 99%